ALTERING FERROUS SULPHATE TO SYNTHETIC GOETHITE - Dessy Amalia; Yuhelda Dahlan; Suganal Suganal (Puslitbang tekMIRA, 2009)
Catalyst is required in any reaction. Coal liquefaction is one of the processes to have need of it. The most common catalyst used in the process is ferrous based catalyst. It is very influenced by pyrhotite, which may be occurred from goethite while goethite can be composed of any iron sources. The research had the use of ferrous sulphate as the main iron source, which was reacted with caustic soda. Parameters on molar ratio of the FeSO4.7H2O/NaOH were 0.2 and 0.33, reaction time applied were 3.5; 6.5 and 17.15 hours, oxygen flow rates of 100; 200; 300; 400 and 500 cc/minute were also observed. The best result was achieved at 0.2 molar ratio of the FeSO4.7H2O/NaOH within 6.5 hours by oxidation process that was containing pure goethite, while 100 cc/minute of oxygen rate was enough for the process to be happened.